(untitled) (Modern education and development, 2025)
The Republic of Uzbekistan has undergone significant political and economic reforms in recent years, with a focus on transitioning towards a more open and democratic society. As part of this transformation, cultural reforms have also been a key priority in shaping the identity and future of the country. This article explores the actual issues of implementing cultural reforms in the development of new Uzbekistan, highlighting the challenges and opportunities that arise in this process.